THE MORPHOLOGICAL STUDY OF FRENCH BORROWED WORDS IN ENGLISH(A CASE STUDY IN A BIOGRAPHY BOOK, MARIA CALLAS,WRITTEN BY ARIANNA STASSINOPOULOS) - Yeni Anggraeni, - (2008)
This research paper is entitled The Morphological Study of French Borrowed Words in English, a case study in a Biography book, Maria Callas, written by Arianna Stassinopoulos. In conducting the study, the writer has to main questions to answer: (1) what morphological processes occur in French borrowed words into English; and (2) how are French words adapted into English. The study employs a descriptive method with a qualitative approach. This method allows the writer to elaborate the collected data. The data are collected from the biography book in the form of textual evidence of kinds of morphological processes the adaptation. In addition, the analyzed words are identified as loanwords based on Duckworth's theory that stated loanwords are borrowed words that was integrated but was not translated. The findings show that there are six kinds of morphological processes found, namely, deletion, addition, change, doubling, singling and combination processes. Moreover, the borrowed words found are adapted to fit the equivalence on English native system. Therefore, English did not borrow French words for granted. English undergoes some processes in borrowing.